Análise genética de escores visuais e sua relação com características reprodutivas de animais da raça Nelore - Paterno, Flavia Motta [UNESP] (2015)
The aim of this study was to estimate the heritability and the genetic, phenotypic and environmental correlations for visual scores (structure, precocity and musculature at weaning and yearling), body weight at 210 and 450 days of age, age at first calving, heifer pregnancy and stayability in Nelore beef cattle participating in a breeding program. The data set consisted on information of 37,826 animals and 88,213 animals in the pedigree. The least square method was used to define the fixed effects for parameters estimation. For traits measured at weaning, four estimation models were tested using single-trait analysis, by means of the restricted maximum likelihood method, using the animal model. Was considered additive and residual random effects (Model 1); additive, maternal and residual random effects (Model 2); additive, maternal permanent environment and residual random effects (Model 3); and additive, maternal, maternal permanent environment and residual random effects (Model 4). Model 1 was used for yearling and reproductive traits. The genetic parameters were determined by single and two-trait analyses using Bayesian methodology. Estimates of average heritability obtained in two-trait analyses, were equal to 0.28, 0.30, 0.27, and 0.28, for structure, precocity and musculature at weaning and body weight at 210 days of age. For yearling traits, the average heritability estimates varied from 0.40 to 0.37 (structure), 0.44 to 0.42 (precocity), 0.39 to 0.37 (musculature), and 0.50 to 0.48 (body weight at 450 days of age). The traits measured at different ages (weaning and yearling) had high genetic correlation: 0.96 for structure, precocity and weight, and 0.94 for musculature. The mean heritability estimate for IPP, 3P and STAY were equal to 0.18, 0.38 and 0.20, respectively. The genetic correlations between visual scores and reproductive traits were favorable, indicating that when selecting animals of greater weight and higher ...